HYDROGEOCHEMICAL COMPOSITION OF SPRINGS AT THE DONNOE FUMAROLE FIELD, MUTNOVSKY VOLCANO (SOUTHERN KAMCHATKA) AND PROBLEMS OF THEIR RELATION WITH SUPERCRITICAL MAGMATIC FLUIDS - Bortnikova S.B.; Sharapov V.N.; Bessonova E.P. (My University, 2007)
The Mutnovsky Volcano (main summit at 52°21 ′ N, 158°16 ′ E; absolute altitude 2323 m) is located 75 km south of the town of Petropavlovsk-Kamchatsky. In terms of explosive activity and heat discharge, this volcano is presently among the most active volcanoes of the Kamchatka volcanic belt. Two merged craters are located to the northwest and west of the summit. Among several known historical eruptions, the last two eruptions (in 1960–1961 and on March 17, 2000) were described in detail. Between eruptions, the volcano is characterized by intense fumarole activity. Three fumarole fields are located in the eastern crater: (1) Verkhnee (i.e., Upper) field with vent temperatures of more than 300°C; (2) Donnoe (i.e., Bottom) field consisting of two relatively separate vents with temperatures up to 150°C; (3) Aktivnaya (i.e., Active) funnel, where powerful gas jets have temperatures up to 570°C.